Reading Activities in English Textbook Based on Revised Bloom’s taxonomy Used in Curriculum 2013 - Dwi Fitri; Syamsul Rizal; Andriadi Andriadi (GHAITSA : Islamic Education Journal, 2024)
The aim of this study was to reveal the description of reading activities in English textbook used at SMP Negeri 15 Kota Bengkulu viewed from Revised Bloom’s Taxonomy framework in curriculum 2013. This research employed descriptive design which focused on the content analysis of reading activities used in English textbook “Bright: An English Course for Junior High School Students”. Therefore, the source of data in this research was an English Textbook used by the English teacher in SMP Negeri 15 Kota Bengkulu. The results showed that the reading activities covered remembering, understanding, applying, analyzing, evaluating, and creating. It means that reading activities in English textbook used in SMP Negeri 15 Kota Bengkulu are suitable to be used in curriculum 2013 because they covered all stages of cognitive domain based on Bloom’s Taxonomy. Although low order activities are considered to limit students’ critical thinking, they are still also important for meaningful learning, improve knowledge and solving some problems in the classrooms. In addition, based on this study there are some considerations of teachers in applying high-order activities in teaching reading i.e. the students’ level language mastery, the goal of the lesson, and time allocation.